European Business Cycle Convergence: Portfolio Similarity and a Declining Home Bias of Private Investors - Jennifer Schneider (Peter Lang International Academic Publishers, 2013)
Is the euro area getting closer with regard to business cycles? The study investigates the linkage between business cycle convergence and financial portfolio choice for a panel of 18 European countries. For this purpose an index is constructed which measures the similarity of investment portfolios. The idea is that financial portfolio choice has an impact on business cycles and contributes to convergence via the consumption-wealth linkage. The background of the analysis is the International Asset Pricing Model (IAPM). The results of fixed effects GMM TSLS estimations confirm the linkage. The effect is higher for country-pairs that are built by one euro area member and one member outside the euro area.
Keywords: 330